Perceptions of Socratic and non-Socratic presentation of information in cognitive behaviour therapy - Heiniger, L.; Clark, G.; Egan, Sarah (Elsevier BV; North Holland, 2018)
© 2017 Elsevier Ltd Socratic Method is a style of inquiry used in cognitive behavioural therapy (CBT) that encourages clients to reflect on their problems and draw conclusions from newly-gained insights. However, assumptions about the superior efficacy of Socratic Method over non-Socratic (didactic) approaches remain largely untested. The aim of this study was to compare the perceived helpfulness of therapists' questions, autonomy supportiveness, likelihood of engaging in therapeutic tasks and preference for Socratic Method versus a didactic approach using a video analogue and ratings of lay observers. The mediating effects of therapeutic alliance and empathy were also examined. Participants (N = 144, mean age = 37, SD = 13) completed an online survey where they rated two videoed therapy analogues. Socratic Method had higher mean scores on perceived helpfulness of therapists’ questions, autonomy supportiveness, and likelihood of engaging in therapeutic tasks and preference than didactic presentation. Perceived helpfulness and preference ratings were higher for Socratic Method after accounting for potential confounders. Perceived therapeutic alliance and empathy both mediated the effect of therapy condition on autonomy and engagement. The findings support the use of Socratic Method in CBT.